2012
DOI: 10.1159/000344022
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Biofilm Composition in Caries and Caries-Free Subjects

Abstract: Background: Certain major pathogens such as Streptococcus mutans, Lactobacillus spp. and others have been reported to be involved in caries initiation and progression. Yet, in addition to those leading pathogens, microbial communities seem to be much more diverse and individually differing. The aim of this study, therefore, was to analyze the bacterial composition of carious dentin and the plaque of caries-free patients by using a custom-made, real-time quantitative polymerase chain reaction assay (RQ-PCR). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 64 publications
4
32
0
2
Order By: Relevance
“…Since previous reviews [2,3], Leptotrichia species have been reported in >124 cases [4,7,16,1869,8793], whereby 30 cases involved L. buccalis [4,8,15,21,34,52,56,70–79,87], 24 cases L. wadei [4,20,24,34,37,42,48,56,67,80,81,90,93], 16 cases L. trevisanii [4,5,9,10,13,14,17,37,87], 14 cases L. hofstadii [34,40,49,56,8184,93], 10 cases L. goodfellowii [4,11,12,21,56,74,85,87], eight cases L. hongkongensis [4,6,18,45,47,56], and five L. shahii [34,56,86]. L. trevisanii and L. wadei bacteremia are extremely rare; clinicians should consider these species in cases involving immunocompromised patients with oral lesions [4,5,13,17,87].…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Since previous reviews [2,3], Leptotrichia species have been reported in >124 cases [4,7,16,1869,8793], whereby 30 cases involved L. buccalis [4,8,15,21,34,52,56,70–79,87], 24 cases L. wadei [4,20,24,34,37,42,48,56,67,80,81,90,93], 16 cases L. trevisanii [4,5,9,10,13,14,17,37,87], 14 cases L. hofstadii [34,40,49,56,8184,93], 10 cases L. goodfellowii [4,11,12,21,56,74,85,87], eight cases L. hongkongensis [4,6,18,45,47,56], and five L. shahii [34,56,86]. L. trevisanii and L. wadei bacteremia are extremely rare; clinicians should consider these species in cases involving immunocompromised patients with oral lesions [4,5,13,17,87].…”
Section: Figurementioning
confidence: 99%
“…It has also been associated with mild liver dysfunction, normal renal function [5], multiple myeloma, non-Hodgkin lymphoma (NHL), diffuse large B-cell lymphoma, post-transplant aplasia, neutropenic fever, myelodysplastic syndrome, mandibular tumor, esophageal carcinoma, and the wound and amniotic fluid of a patient with respiratory difficulties [4,5,9,10,13,14,17,37,87]. …”
Section: Brief Additional Clinical Information On Leptotrichia Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…1 It results from a demineralization process in which acidogenic and acidophilic bacteria embedded in a mature, well-arranged biofilm degrade the tooth substance, ultimately leading to cavitation. 2 Although several studies have related the participation of other bacteria in the pathogenesis of dental caries, 2,3,4,5 Streptococcus mutans plays a central role in the development of cariogenic biofilms, mainly due to its acid-tolerant and Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript. acidogenic characteristics.…”
Section: Introductionmentioning
confidence: 99%